Molecular cytogenetic identification and nutritional composition evaluation of newly synthesized Triticum turgidum-Triticum boeoticum amphiploids (AABBAbAb) - Liu, Xin; Jiang, Xiaomei; Zhang, Junqing; Ye, Hong; Shen, Mang; Wu, Lei; Miao, Yongping; Chen, Longyu; Zhou, Ke; Hao, Ming; Jiang, Bo; Huang, Lin; et al. (Frontiers in Plant Science, 2023)
Triticum boeoticum Boiss. (AbAb, 2n = 2x = 14) is a wheat-related species with the blue aleurone trait. In this study, 18 synthetic Triticum turgidum-Triticum boeoticum amphiploids were identified, which were derived from crosses between T. boeoticum and T. turgidum. Three probes (Oligo-pTa535, Oligo-pSc119.2, and Oligo-pTa713) for multicolor fluorescence in situ hybridization (mc-FISH) were combined with genomic in situ hybridization (GISH) to identify chromosomal composition. Seven nutritional indices (anthocyanins, protein, total essential amino acids TEAA, Fe, Zn, Mn and Cu) were measured, and the nutritional components of 18 synthetic amphiploids were comprehensively ranked by principal component analysis (PCA). The results showed that all three synthetic amphiploids used for cytological identification contained 42 chromosomes, including 14 A, 14 B, and 14 Ab chromosomes. The average anthocyanin content was 82.830 μg/g to 207.606 μg/g in the whole meal of the 17 blue-grained lines (Syn-ABAb-1 to Syn-ABAb-17), which was obviously higher than that in the yellow-grained line Syn-ABAb-18 (6.346 μg/g). The crude protein content was between 154.406 and 180.517 g/kg, and the EAA content was 40.193-63.558 mg/g. The Fe, Zn, Mn and Cu levels in the 17 blue-grained lines were 60.55 to 97.41 mg/kg, 60.55-97.41 mg/kg, 35.11 to 65.20 mg/kg and 5.74 to 7.22 mg/kg, respectively, which were higher than those in the yellow-grained line. The contribution of the first three principal components reached 84%. The first principal component was mainly anthocyanins, Fe, Zn and Mn. The second principal component contained protein and amino acids, and the third component contained only Cu. The top 5 Triticum turgidum-Triticum boeoticum amphiploids were Syn-ABAb-11, Syn-ABAb-17, Syn-ABAb-5, Syn-ABAb-8 and Syn-ABAb-4. These amphidiploids exhibited the potential to serve as candidates for hybridization with common wheat, as indicated by comprehensive score rankings, toward enhancing the nutritional quality of wheat.